2005
DOI: 10.1097/01.fjc.0000176728.74690.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicorandil on Monocrotaline-Induced Pulmonary Arterial Hypertension in Rats

Abstract: We investigated whether nicorandil might prevent and reverse monocrotaline (MCT)-induced pulmonary arterial hypertension. Rats were injected with 50 mg/kg of MCT subcutaneously and randomized to either 7.5 mg/kg/d of nicorandil in drinking water or placebo for 3 weeks. Animals that were treated with MCT and survived for 3 weeks were assigned to either nicorandil or placebo. Nicorandil markedly attenuated pulmonary arterial hypertension with severe structural remodeling of the pulmonary vessels. The survival ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…This enzyme plays important roles in inhibiting platelet aggregation and relaxing vascular smooth muscle. Previous studies have reported that nicorandil prevented the downregulation of eNOS in the lung tissue of a rat model of monocrotaline-induced pulmonary arterial hypertension 33 and in the hearts of Dahl salt-sensitive hypertensive rats. 9 However, nicorandil did not increase eNOS mRNA levels, eNOS phosphorylation or nitrite production in the present study (Figure 6).…”
Section: Discussionmentioning
confidence: 90%
“…This enzyme plays important roles in inhibiting platelet aggregation and relaxing vascular smooth muscle. Previous studies have reported that nicorandil prevented the downregulation of eNOS in the lung tissue of a rat model of monocrotaline-induced pulmonary arterial hypertension 33 and in the hearts of Dahl salt-sensitive hypertensive rats. 9 However, nicorandil did not increase eNOS mRNA levels, eNOS phosphorylation or nitrite production in the present study (Figure 6).…”
Section: Discussionmentioning
confidence: 90%
“…There is a growing consensus that there are reduced NO levels in the pulmonary arterial walls in human and experimental PAH, even though the levels of eNOS protein have been variably reported as unchanged, decreased, or even increased (24,34,40,41,53,67,76,83,101). It is also now clear that the extracellular NO derives from cell-surface caveolar eNOS and that intracellularly active eNOS produces NO in subcellular compartments from where the NO does not reach the extracellular space (27,37).…”
Section: Consequences Of a Trafficking Block: Reduced Caveolar No Witmentioning
confidence: 99%
“…Findings of studies on cardiovascular disease have shown that nicorandil protects endothelial function (14) and enhances eNOS expression (16). In a monocrotaline-induced pulmonary arterial hypertension model, similar effects of nicorandil were identified (15). Therefore, in the present study, expression of eNOS was determined and regulatory mechanisms were explored.…”
Section: Discussionmentioning
confidence: 75%
“…A number of studies (14)(15)(16) have demonstrated the critical role of eNOS in PH, particularly in the maintenance of endothelial function. Findings of studies on cardiovascular disease have shown that nicorandil protects endothelial function (14) and enhances eNOS expression (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation